Titrimetric Estimation of Calcium Contents in Some Selected Fruits of Wurkum Market, Makurdi, Benue State - E.Y, Yusuf; A, Abdullateef; O., Samuel (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study was carried out, to investigate the concentration of calcium in five different fruits samples of locally produced and commonly consumed fruits namely pineapple, banana, pear, watermelon and plantain, within Makurdi, Benue state, North-Central Nigeria. The samples were analyzed in triplicates using the method of EDTA titration. The result showed highest mean level of calcium in banana (28.80mg/100g) followed by plantain (28.04mg/100g), watermelon (23.61mg/100g), pineapple(23.16mg/100g) and pear (25.13mg/100g), however it is advised that those who have Hypocalcaemia eat extra banana and plantain to increase their body’s calcium level. A chronic calcium deficit can cause abnormalities in the teeth, cataracts changes in the brain and osteoporosis, which weakens the bones.